Correlation analysis of financial conflicts of interest and favourability of results or conclusions in addiction medicine systematic reviews and meta-analysis. Issue 8 (29th August 2022) - Vassar, Matthew; Shepard, Samuel; Demla, Simran; Tritz, Daniel
Abstract : Objective: To quantify conflicts of interest, assess the accuracy of authors self-reporting them, and examine the association between conflicts of interest and favourability of results and discussions in addiction medicine systematic reviews. Design: A search was performed on Medline (Ovid) from January 2016 to 25 April 2020 to locate systematic reviews and meta-analyses focused on treatments of addiction disorders using a systematic search strategy. Data were extracted from each systematic review, including conflict of interest statements, authorship characteristics and the favourability of the results/conclusion sections. A search algorithm was used to identify any undisclosed conflicts of interest on the Open Payments Database (Dollars for Docs), Dollars for Profs, Google Patents/United States Patent and Trade Office, and prior conflict of interest statements in other published works from these authors. Results: The search identified 127 systematic reviews, representing 665 unique authors. Of the 127 studies, 81 reported no authors with conflicts of interest, 28 with 1 or more conflict, and 18 had no conflict of interest statement. Additional non-disclosed conflicts of interest were found for 34 authors. There were 69 reviews that had at least one author with a conflict of interest. Of the 69 reviews, 14 (20.3%) reported favourable results and 26 (37.7%) reported favourable discussion/conclusions with no statistically significant association. A subanalysis was performed on publications with only US authors (51) with 35 (68.9%) having at least 1 conflict of interest. US authored studies that had a conflict of interest favoured the results (p = <0.001) and discussion/conclusion (p = 0.018) more often. Conclusion: Although multiple undisclosed financial conflicts of interest were found, there was no correlation with the favourability of the results or discussion/conclusions across all addiction medicine systematic reviews. Further research needs to be done on US-based publications and encourage disclosure systems worldwide to provide more accurate reporting.